2006
DOI: 10.1161/01.atv.0000238351.82900.7f
|View full text |Cite
|
Sign up to set email alerts
|

Microcirculatory Hemodynamics and Endothelial Dysfunction in Systemic Lupus Erythematosus

Abstract: Objective-Impaired flow-mediated dilation (FMD) occurs in disease states associated with atherosclerosis, including SLE.The primary hemodynamic determinant of FMD is wall shear stress, which is critically dependent on the forearm microcirculation. We explored the relationship between FMD, diastolic shear stress (DSS), and the forearm microcirculation in 32 patients with SLE and 19 controls. Methods and Results-DSS was calculated using (mean diastolic velocityϫ8ϫblood viscosity)/baseline brachial artery diamete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 54 publications
4
41
2
1
Order By: Relevance
“…[38][39][40] Techniques providing a global assessment of the circulation may not capture, or cannot localise, findings to a specific site or target organ of interest in the arterial system. 29 These results support previous findings 18,41 indicating that comprehensive spectral analysis of retrobulbar flow velocity waveforms can identify altered structure or tone in the ocular microcirculatory bed at an early preclinical stage. The technique represents a sensitive, non-invasive assessment tool with potential to track and monitor the effect of therapeutic interventions in relation to the development of complications with risk factors for cardiovascular disease.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…[38][39][40] Techniques providing a global assessment of the circulation may not capture, or cannot localise, findings to a specific site or target organ of interest in the arterial system. 29 These results support previous findings 18,41 indicating that comprehensive spectral analysis of retrobulbar flow velocity waveforms can identify altered structure or tone in the ocular microcirculatory bed at an early preclinical stage. The technique represents a sensitive, non-invasive assessment tool with potential to track and monitor the effect of therapeutic interventions in relation to the development of complications with risk factors for cardiovascular disease.…”
Section: Discussionsupporting
confidence: 86%
“…Pathological change in the microvasculature in diabetes, including basement membrane thickening, may have little effect on altering flow resistance, 37 but may influence the pattern of wave reflection and thus structure of the flow velocity profile. 18 The ultimate shape of flow and pressure waveforms reflects the interaction between the output generated by the left ventricle and the magnitude and timing of wave reflection from impedance mismatches arising predominantly from reflection sites from microcirculatory beds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the resistive index failed to discriminate between groups. Quantifiable differences in the flow velocity waveform were most evident in waveforms recorded in the immediate proximity of the ophthalmic artery microvascular bed compared with recordings made in the more proximal carotid conduit artery, a finding we have previously reported in patients with systemic lupus erythematosus (51). Propagating waves can add destructively as well as constructively, and the effects of wave reflection in altering the Doppler flow velocity waveshape depend on the distance between recording and reflecting sites, the magnitude of wave reflection, the speed of the pulse wave, and the degree of attenuation and energy dissipation produced by blood viscosity and damping by the vessel walls (6,22,39).…”
Section: Discussionsupporting
confidence: 57%
“…Techniques designed to assess endothelial function are based on measurement of brachial artery reactivity in response to changes in blood-flow caused by passive congestion (flow-mediated vasodilatation, which is dependent on endothelial function) (Corretti et al, 2002). Studies performed in SLE patients documented an impaired endothelial function and this fact was attributed to reduced nitric oxide bioavailability resulting from increased oxidative stress in the course of SLE (El-Magadmi et al, 2004;Kiss et al, 2006;Wright et al, 2006). Furthermore, impairment of endothelial function remained significant even after adjustment for other classic atherosclerosis risk factors and the authors suggested that SLE is an independent risk factor for endothelial dysfunction (El-Magadmi et al, 2004).…”
Section: Atherosclerosis In Systemic Lupus Erythematosus -The Backgroundmentioning
confidence: 99%